The Evolution Of Management Information Systems In The Ag Of Big Data And Analytics (Journal of Namibian Studies : History Politics Culture, 2022)
This research explores the evolution and impact of Management Information Systems (MIS) in the context of Big Data and Analytics. Initially, MIS focused on basic data processing and transactional tasks. With technological advancements, its scope expanded to encompass decision support, resource management, and strategic planning, becoming crucial for informed decision-making and efficient resource management in businesses. The advent of Big Data, characterized by vast volumes of structured and unstructured data from diverse sources, has revolutionized MIS. It posed new challenges but also provided opportunities for integrating advanced analytics into MIS frameworks.The study emphasizes how Big Data and Analytics have transformed business processes, decision-making, and strategic planning. It highlights the integration of predictive analytics, machine learning, and data mining, which have become essential in extracting meaningful insights from large data sets and understanding market trends and customer preferences. The research objectives include analyzing the historical development of MIS, assessing the impact of Big Data and Analytics, identifying challenges and opportunities presented by this integration, predicting future trends considering emerging technologies like AI and IoT, and providing best practices for effectively utilizing MIS in the era of Big Data and Analytics.